The Effect of a Turkey Berry (Solanum torvum)-Fortified Biscuit on the Hemoglobin Level and Cognitive Performance of Adolescent Females in the Ahafo Region of Ghana: A Pilot Study - Appiah, Abigail Owusuaa; Tandoh, Marina Aferiba; Puotege, Pepertual Suglo; Edusei, Anthony Kwaku (International Journal of Food Science, 2023)
Anemia is a public health problem that affects about 50% of adolescent females in sub-Saharan Africa. Anemia can negatively affect the overall growth, cognitive performance, and productivity of school-going adolescents. This pilot study assessed the impact of Solanum torvum-fortified biscuits on hemoglobin levels and cognitive performance of school-going adolescent females. A cluster randomized controlled, open labeled trial was undertaken among four basic schools in the Ahafo Region of Ghana. Out of the 169 participants, 151 (intervention=83, control=68) adolescent females completed the trial. The intervention and control groups were made up of two schools each. The participants in the intervention and control groups received a total of 30 turkey berry-fortified biscuit supplementation or 30 placebos for a period of six weeks, respectively. The hemoglobin levels and cognitive test scores were obtained before and after the intervention. The number of anemic cases and low cognitive performance among the female adolescents in the intervention group reduced by 23.8% and 8.7%, respectively. There was a positive impact on the hemoglobin levels and cognitive performance of the intervention group. For every unit of turkey berry-fortified biscuit consumed by the intervention group, there was a 0.945 unit increase in hemoglobin level (p=0.001) and a 2.796 unit increase in cognitive performance (p=0.005). The turkey berry-fortified biscuit significantly reduced anemia prevalence and improved cognitive performance among the adolescent girls. Therefore, its potential in the management of anemia and improvement of cognition could be explored.